2016
DOI: 10.1080/09654313.2016.1159666
|View full text |Cite
|
Sign up to set email alerts
|

Bringing owls to Athens? The transformative potential of RIS3 for innovation policy in Germany's Federal States

Abstract: This paper reports on the impact of smart specialization policies in an economically already well-developed and politically experienced environment. Arguably, German regions were quite experienced with strategic innovation policy long before the ex-ante conditionality was imposed and their first reaction to it was accordingly reserved. Nonetheless, our case studies illustrate that the process related to the development of regional innovation strategies has in many German regions led to advances in methodology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 14 publications
(11 reference statements)
0
18
0
2
Order By: Relevance
“…Peters, 2008;Beise and Stahl, 1999), as well as innovation policies (e.g. Kiese, 2008;Kiese and Wrobel, 2011;Kroll et al, 2016). To the best of our knowledge, the regional (knowledge) specialisation within Germany has been studied only by Suedekum (2006), who found that between 1993 and 2001 there was neither a process of regional specialisation nor one of the geographical concentration of industries in Germany.…”
Section: Theoretical Background: Innovation Specialisation and Relatmentioning
confidence: 99%
See 2 more Smart Citations
“…Peters, 2008;Beise and Stahl, 1999), as well as innovation policies (e.g. Kiese, 2008;Kiese and Wrobel, 2011;Kroll et al, 2016). To the best of our knowledge, the regional (knowledge) specialisation within Germany has been studied only by Suedekum (2006), who found that between 1993 and 2001 there was neither a process of regional specialisation nor one of the geographical concentration of industries in Germany.…”
Section: Theoretical Background: Innovation Specialisation and Relatmentioning
confidence: 99%
“…As part of the former German Democratic Republic, the major focus was on heavy industry and there were almost no EPO patent applications prior to 1990. Saxony was successful in attracting a number of major manufacturing companies, as well as institutes of national research organisations, to the region, as it carried out the most successful transformation among Eastern German regions (Kroll et al, 2016). The automobile, machinery and metal production industries continue to be important, along with the significant growth of the electronics sector.…”
Section: Oberes Elbtal/osterzgebirgementioning
confidence: 99%
See 1 more Smart Citation
“…The article "Facilitating an entrepreneurial discovery process for smart specialisation. The case of Poland" by Mieszkowski and Kardas (2015) approaches question around the extent to which initiatives such as prospective programmes, strategic research and development programmes and sector-based Vittoria and Napolitano (2016) Vittoria and Napolitano (2016) Kroll, Böke, Schiller, and Stahlecker (2016) Bečić and Švarc (2015) Bečić and Švarc (2015) Bečić and Švarc (2015) Kroll et al (2016) Healy (2016) Cooke (2016) Capello and Lenzi (2015) Capello and Lenzi (2015) Capello and Lenzi (2015) Reimeris (2016) Morgan (2016) Healy (2016) Camagni and Capello (2013) Camagni and Capello (2013) Camagni and Capello (2013) Cooke (2016) Kroll et al (2016) Vittoria and Napolitano (2016) Carayannis and Grigoroudis (2015) Carayannis and Grigoroudis (2015) Carayannis and Grigoroudis (2015) Capello and Lenzi (2015) Capello and Lenzi (2015) Healy (2016) Clar and Sautter (2014) Clar and Sautter (2014) Clar and Sautter (2014) Fabbri (2016) Fabbri (2016) Estensoro and Larrea (2016) Cooke (2016) Cooke (2016)...…”
Section: Business Discovery (Cluster 1)mentioning
confidence: 99%
“…Böke, Schiller, and Stahlecker (2016) Bečić and Švarc (2015) Bečić and Švarc (2015) Bečić and Švarc(2015)Kroll et al (2016) …”
mentioning
confidence: 99%